HAKIKAT PENDIDIKAN INKLUISI ANAK USIA DINI (PAUD) - muliya putra, hapindo; Andriani, Opi; desrianda, indah; antika, serli afri (Program Studi Pendidikan Vokasi Seni Kuliner, 2024)
This research aims to examine the nature of early childhood education (PAUD) as the main foundation in child development which includes physical, cognitive, social, emotional and moral aspects, as well as providing recommendations for educators, parents and policy makers to create a learning environment that optimal. This research uses a qualitative method with a library study approach, where secondary data is obtained from various trusted sources, such as scientific journals, books and official documents. Data analysis was carried out using the Miles and Huberman technique, which includes data reduction, data presentation, and drawing conclusions. The research results show that PAUD plays an important role in providing stimulation according to children's developmental stages, preparing them for formal education, and forming character and essential life skills. Quality early childhood education can foster self-confidence, creativity and sustainable learning motivation, so that it becomes a strategic investment for individual success and national progress.